Systemic iron availability differentially shapes tumor and brain iron handling in a sex-dependent manner in glioblastoma - Emily Tufano; Kondaiah Palsa; Rebecka O. Serpa; Timothy B. Helmuth; Gabriela Remit-Berthet; Sara Mills-Huffnagle; Mathias Kant; Aurosman Sahu; James R. Connor (PLoS ONE, 2026)
Iron is essential for normal physiological function, yet dysregulation of iron metabolism is increasingly recognized as a hallmark of cancers such as glioblastoma (GBM). Recent clinical evidence suggests that systemic iron deficiency anemia (IDA) negatively impacts GBM outcomes in a sex-dependent manner, but the mechanisms linking systemic iron availability to tumor iron metabolism remain poorly understood. Here, we interrogate the impact of systemic iron through dietary modulation (control, iron deficiency (ID), and high iron diets), stratified by sex, on tumor iron handling and GBM outcomes utilizing an immune competent (C57BL/6) GBM (GL261) mouse model. Subsequently, we analyzed clinical samples to evaluate translational value. In the preclinical study, we show that iron deficiency decreased survival in males but conferred a slight survival advantage in females, consistent with prior clinical trends. Among circulating iron markers, only ferritin light chain (FTL), but not ferritin heavy chain (FTH) or serum iron, positively correlated with survival in males but not females. In the brain, contralateral iron levels reflected dietary iron status in males but not females, further supporting sex-dependent regulation of local and circulating iron. Notably, tumor iron content remained unchanged in males but was significantly elevated in ID female tumors, complemented by increased transferrin receptor (TfR1) and FTH expression. In clinical GBM samples, we observed non-statistically significant but similar survival trends across varying iron and ferritin levels, suggesting potential translational relevance of our exploratory model. These findings demonstrate that systemic iron availability exerts a sex-specific effect on tumor iron handling, highlighting a critical relationship between systemic and tumor iron regulation in GBM.